Persons of the market: conservatism, corporate personhood, and economic theology - Musgrave, Kevin (Michigan State University Press, 2022)
"Taking corporate personhood as a starting point, Persons of the Market observes the complex and entangled nature of Christian theology and liberal capitalism to shed new light on the historical relationship between the two and to better comprehend their seemingly odd marriage in contemporary politics"--